Association of socio-demographic background and home food environment with body weight status among primary school students in Bangi, Malaysia - Rathuan, Rina Syahira (2021)
Childhood obesity and undernutrition is a global epidemic issue. Home food environment is an important aspect that may influence children’s body weight status. The aim of this study is to identify the association between socio-demographics and home food environment (HFE) with body weight status in primary school students in Bangi, Malaysia. There were 398 children (43.5% males and 56.5% females) aged 7- 11 years old (mean age of 9.04±1.41 years) and their parents (66.6% mothers and 33.4% fathers) from eight randomly selected primary schools participated in this study. Parents were asked to complete a self-administered questionnaire on sociodemographic background, feeding practices and food availability. For standard one to three, children were interviewed to obtain information on parenting styles and physical activity level, while for standard four to five, the questionnaire was self-administered with the help of researcher in the class. Weight and height of the children were assessed, and BMI-for-age z-score (BAZ) was calculated by using WHO Anthroplus Software. Overweight and obesity prevalence was 17.8% and 13.1% respectively. Whereas, prevalence of thinness and severe thinness was 3.8% and 0.2% respectively. A majority of the parents (61.3%) in this study practiced authoritative parenting style. An increasing age is found to lead to an increase in children's BMI. While, female students were observed to have a lower BMI compared to male. Parent’s increasing restriction for weight control (β=0.22, p<0.05) and decreasing pressure to eat (β=-0.19, p<0.05) increased childhood overweight and obesity risk. This study emphasizes the importance of involving parents in the weight intervention programs for children. Future longitudinal studies are necessary to explore the association of home food environment factors and children’s weight status.